The Efficiency of Information Technology and its Role of e-HRM in the Palestinian Universities - Mazen J. Al Shobaki; Samy S. Abu Naser; Youssef M. Abu Amuna; Suliman A. El Talla (International Journal of Engineering and Information Systems (IJEAIS), 2017)
The research aims to identify the efficiency of information technology and its role in human resources management electronically at universities in the Gaza Strip, and the population of the study consists of IT staff centers, where the number reached 35 employees working in universities in the Gaza Strip,. The researchers used the questionnaire as a tool for the study, descriptive and analytical approach was used to achieve the objectives of the study, (SPSS) program has been used to analyze the study data. The results of the study showed that there is agreement from the sample of the study on the availability of infrastructure in the IT center, which is statistically significant at (0.05), where the relative weight reached (73.97%) and the arithmetic mean (7.4). The results showed that the sample was highly agreeable, as all the results were statistically acceptable and above the arithmetic mean (6). The study stressed that the cooperation of information technology centers of private sector institutions is few and limited. The results confirmed the availability of management information systems for all administrative systems in a medium way, and that these systems are moderately adequate to build an electronic management system. The study reached several recommendations, the most important of which is the need to provide financial support to IT centers for their importance in the process of change to electronic management. The need to develop computerized management information systems to cover all administrative aspects. The need to develop e-HRM in universities, because they have a key role in the success of the process of transition to electronic management. The importance of the adoption of internal electronic correspondence instead of paper, which contributes significantly to reduce administrative financial expenses, and the speed of completion of work. The need to integrate computerized management information systems and work to link what is currently fully present as a beginning to a gradual transition to electronic management.
Keywords: 330; efficiency of information technology; human resources management electronically; Palestinian universities